Impaired Differentiation of Langerhans Cells in the Murine Oral Epithelium Adjacent to Titanium Dental Implants - Heyman, Oded; Koren, Noam; Mizraji, Gabriel; Capucha, Tal; Wald, Sharon; Nassar, Maria; Tabib, Yaara; Shapira, Lior; Hovav, Avi-Hai; Wilensky, Asaf (Frontiers in Immunology, 2018)
Peri-implantitis is a destructive inflammatory process affecting tissues surrounding dental implants and it is considered a new global health concern. Human studies have suggested that the frequencies of Langerhans cells (LCs), the main antigen presenting cells (APCs) of the oral epithelium, are dysregulated around the implants. Since LCs play a role in regulating oral mucosal homeostasis, we studied the impact of dental titanium implants on LC differentiation using a novel murine model. We demonstrate that whereas the percentage of LC precursors (CD11c+MHCII+) increased in the peri-implant epithelium, the frequencies of LCs (CD11c+MHCII+EpCAM+langerin+) were significantly reduced. Instead, a population of partially developed LCs expressing CD11c+MHCII+EpCAM+ but not langerin evolved in the peri-implant mucosa, which was also accompanied by a considerable leukocyte infiltrate. In line with the increased levels of LC precursors, expression of CCL2 and CCL20, chemokines mediating their translocation to the epithelium, was elevated in the peri-implant epithelium. However, expression of TGF-β1, the major cytokine driving final differentiation of LCs, was reduced in the epithelium. Further analysis revealed that while the expression of the TGF-β1 canonical receptor ALK5 was upregulated, expression of its non-canonical receptor ALK3 was decreased. Since titanium ions releasing from implants were proposed to alter APC function, we next analyzed the impact of such ions on TGF-β1-induced LC differentiation cultures. Concurring with the in vivo studies, the presence of titanium ions resulted in the generation of partially developed LCs that express CD11c+MHCII+EpCAM+ but failed to upregulate langerin expression. Collectively, these findings suggest that titanium dental implants have the capacity to impair the development of oral LCs and might subsequently dysregulate immunity in the peri-implant mucosa.